Modemmethodsofcomputerdiagnosticsdentalocclusionand TMJ, craniomandibular system and facial aesthetics - O. O. Yanushevich; S. D. Arutyunov; M. M. Antonik (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
To date, the traditional methods of instrumental diagnosis of occlusion and TMJ - quite time consuming and difficult to perform.Requires a very high qualification of experts capable of conducting such a diagnosis. In this regard, the existing and evolving digital technologycan not only producevarious removable and nonremovableorthodonticand orthopedicdesign, but also allow for a precise and easier to perform, diagnoseocclusion of dentition with the biomechanicsof the temporomandibular joint and the aesthetics of the patient's face.